Temperature-dependent solid material properties of GRCop-42 for an additively manufactured liquid rocket engine LOx cooling channel - Monokrousos, Nikos; Könözsy, László Z.; Pachidis, Vassilios; Sozio, Ernesto; Rossi, Federico (University of Miskolc, 2024)
Recent technological developments in the field of Additive Manufacturing (AM) provide a number of opportunities for the utilisation of high-performance copper alloys for aerospace applications. The additively manufactured LOx/LNG DemoP1 aerospike engine demonstrator designed by Pangea Aerospace is a characteristic example based on the Direct Metal Laser Sintering (DMLS) technology. The aerospike engine thrust chamber and LOx cooling channels are manufactured using GRCop-42 material powder, a Cu-Cr-Nb based copper alloy developed by the National Aeronautics and Space Administration (NASA) for the regenerative cooling technology of high thermal demand thrust chambers and nozzles. In the current work temperature-dependent correlations are derived for the density, specific heat capacity at constant pressure and thermal conductivity of the GRCop-42 material. The correlations for the solid material properties are then introduced into the ANSYS Fluent 2023 R2 Computational Fluid Dynamics (CFD) package and their capabilities are investigated for the characterisation of the flow-field characteristics of the LOx flow in the cooling channel. The numerical solution of the coolant flow in the AM cooling channel is compared against experimental data of the DemoP1 engine demonstrator. The main objective of this study is to provide a realistic physical description of the temperature-dependent properties of the AM solid material in high heat flux applications where the material properties are mostly considered as constant in previous studies.
XXXІI International Scientific and Practical Conference “Information Technologies: Science, Engineering, Technology, Education, Health (MicroCAD-2024)” 22-25 May 2024, Kharkiv, Ukraine
Keywords: Aerospike engine; Additive Manufacturing; LOx cooling channel; GRCop-42 copper alloy; Material properties